Interspecific competition constrains local abundance in highly suitable areas. Issue 10 (21st July 2020) - Braz, Alan Gerhardt; de Viveiros Grelle, Carlos Eduardo; de Souza Lima Figueiredo, Marcos; Weber, Marcelo de Moraes
Abstract : Sites with high environmental suitability for species' occurrence, in terms of abiotic conditions, may hold populations with higher local abundances by increasing reproductive and survival rates and decreasing extinction rate. Interspecific competition, however, may affect this relationship. Here we tested the hypothesis that local abundance of the gray slender opossum Marmosops incanus is affected by the local richness of potential competitors and environmental suitability derived from ecological niche models (ENMs). We also discuss the ability of distinct modelling methods to predict species' abundance. We compiled occurrence records and information about M. incanus ' relative abundance from museums and published articles. Environmental suitability was derived from five algorithms using seven environmental predictors. To assess our hypothesis, we chose the best statistical models among generalised linear models and quantile regressions, and then tested whether the effects of richness of competitors on local abundance are stronger under highly suitable conditions. We found that environmental suitability given by presence‐only methods are positively related to the maximum abundance of M. incanus . That is, species' local abundance is low when suitability is low but can be either low or high when suitability is high. The richness of competitors, in turn, explains the abundance variation within sites with high environmental suitability. We strongly recommend that the relationship between abundance and suitability must be carefully interpreted when using ENMs to predict species' distribution because biotic interactions can be the main driver of local abundance within highly suitable environments.